Gender Injustice in Photocopier Movie by Wregas Bhanuteja - Pratama, Yudha; Chitra, Bima Prana; Ilmi, Djauzi (Journal of English Language and Education, 2024)
This study aims to describe gender injustice in Photocopier movie by Wregas Bhanuteja using feminist literary criticism theory and Fakih’s theory of gender to explain the patriarchal culture that causes gender injustice in this movie. This research was conducted through the qualitative research method. The data source in this research is Photocopier movie by Wregas Bhanuteja on Netflix. The steps for data collection with qualitative techniques, library techniques, reading techniques, and note-taking techniques. The form of data in this research is the form of sentences, dialogues, and discourses contained in Photocopier movie by Wregas Bhanuteja, chosen according to the main problem in this study, namely Gender Injustice in Photocopier movie by Wregas Bhanuteja. The results obtained 5 forms of gender injustice by Fakih’s theory namely: marginalization, subordination, stereotype, violence, and double burden which are influenced by the patriarchal culture where men dominate and are powerful toward women